MODIFIED TRAFFIC SIGNAL PHASING AT TRAFFIC WARDEN CONTROLLED INTERSECTION TO ACCOMMODATE PEDESTRIAN TRAFFIC IN ILORIN METROPOLIS, NIGERIA (Nigerian Journal of Technology, 2015)
The study addresses the nervous anxiety always noticed in pedestrians as they cross at a 4-arm, Traffic Warden Control intersection in Ilorin metropolis, Nigeria. Two of the approaches (Challenge and Unity) are dualised multilanes while the other two (Obbo and CocaCola) are two-lane non-dualised. The present 4-phase traffic control scheme does not give consideration to pedestrian crossing. The geometric layout and the existing traffic management practice at the intersection were determined and a pedestrian traffic survey was conducted. The critical pedestrian volume of 171 pedestrians/hr was obtained on Challenge approach. Using an average walking speed of 1.2 m/s and a crosswalk width of 3 m a pedestrian crossing time of 787.88 seconds within one hour is obtained as being adequate for the critical approach.  A 5-phase scheme is proposed with the fifth phase being an all-stop exclusive phasing for pedestrian movements. Crosswalk should be introduced to concentrate pedestrian crossing activity at a specific location thereby positioning pedestrians to be more visible to traffic wardens and motorists.  http://dx.doi.org/10.4314/njt.v35i1.4